Exploring the evolution and hidden large-scale structures of galaxies with MeerKAT HI surveys - Rajohnson, Sambatriniaina Hagiriche Aycha (Department of Astronomy, 2025)
Building upon previous high-resolution and high-sensitivity H I surveys conducted over narrow angles of the sky, such as the COSMOS H I Large Extragalactic Survey (CHILES), a new era has begun with the emergence of SKA Pathfinders such as MeerKAT and ASKAP. Deep systematic interferometric H I surveys of unprecedented sensitivity and resolution over very wide angles of the sky are now possible. In this thesis, I use the capabilities of MeerKAT to explore H I galaxy scaling relations and investigate concealed large-scale structures (LSS) linked to dynamically significant structures in the Southern Zone of Avoidance (ZOA). To achieve these objectives, I worked on three blind systematic H I surveys conducted with the 4k L-band data from the complete MeerKAT64 array: the MIGHTEE-H I Early Science data, the Vela SARAO MeerKAT Galactic Plane Survey (Vela– SMGPS), and the MeerKAT Vela Supercluster survey (Vela–H I). As a first step, I validated the MIGHTEE-H I Early Science data covering a total of ⇠5 deg2, distributed across three XMMLSS fields (⇠3.5 deg2) and one COSMOS field (⇠1.5 deg2). The spectral line data achieved 1200⇥1000 and 14.500⇥1100 angular resolutions, with an rms sensitivity of 81 and 44 `Jy beam–1 per 44.1 km s–1 channel, for a total observing time of 13 and 17 hours per XMMLSS and COSMOS field, respectively. Following visual source identification and morphological classification, the sample comprised 276 galaxies – 176 spirals, 72 irregulars, 19 mergers, and 9 early-type galaxies. To independently verify the derived H I properties, I cross-referenced fluxes from COSMOS detections with ALFALFA galaxies, revealing agreement for high-signal-to-noise ratio sources. As an application of the data verification process, I constructed the H I size-mass relation, investigating potential systematic eects present in the early data. This relation was derived for the first time from a uniform interferometric sample, reaching an unprecedented redshift range of z ⇠ 0.084. Based on a subsample of 204 galaxies, the relation was found to be consistent with the literature at z ⇠ 0 and indicated that in the absence of significant environmental influences, gas distribution and mean surface mass density within galaxy discs have remained relatively stable over the past one billion years. A 10% intrinsic variation (0.054 ± 0.003 dex) in the H I size at a given H I mass was observed, but no evidence for evolution over the explored redshift range. I performed a detailed census to blindly map signatures of hidden LSS in the Vela region, aiming to narrow down the ZOA in redshift space. This unexplored area hosts the enigmatic Vela Supercluster (VSCL), with its potential merging walls and an inner core obscured in the innermost ZOA. The location of the VSCL is also essential for addressing persistent bulk flow discrepancies. I pursued a two-phase mapping of the VSCL, with a focus on identifying its gas-rich spirals. Firstly, using data from Vela–SMGPS, which surveyed a narrow strip covering 90 deg2 (260  ✓  290, –2  b  1). I imaged 157 individual pointings with a total observing time of ⇠211 hours. This produced 10 contiguous mosaics with an average rms of 0.39 mJy beam–1 per 44 km s–1 channel and an angular resolution of 3000⇥2700 (±100). Secondly, the MeerKAT Vela–H I survey was designed to explicitly fill the gaps above and below the Galactic Plane (GP) between Vela–SMGPS and prior Vela spectroscopic survey regions (263  ✓  284, –6.7  b  –2, 1  b  6.2). I processed the 667 Nyquist-sampled fields and generated 32 mosaics. With 67 hours of observations over a 242 deg2 area, the survey reached an average rms of 0.74 mJy beam–1 per 44 km s–1 channel for the beam size of 3800⇥3100 (±300). By focusing on the mostly RFI-free band of 250 < Vhel < 25000 km s–1, I identified 843 and 719 heavily obscured galaxy candidates in Vela–SMGPS and Vela–H I, respectively, most of which were previously unknown. When comparing the distribution to simulations based on the SKA H I-science method which assumes a homogeneous distribution, and examining onsky distributions, a total of six overdensities were observed. With regard to VSCL, the new detections hint at the presence of two wall-like overdensities at 16000 – 19000 km s–1 (W1) and 19000 – 23000 km s–1(W2). These may well intersect within the longitude range 270  ✓  279 at the lowest latitudes. Other major overdensities include the confirmation of the presence of the Hydra/Antlia wall traversing the GP at ✓ ⇠ 280 ± 2 at Vhel ⇠ 2500 – 4000 km s–1 and the discovery of a 30 long, narrow filament in the GP at ⇠12000 km s–1. By only considering the complete sample from Vela–SMGPS and Vela–H I, I calculated the H I mass function (HIMF) of the two surveys in an attempt to quantify these VSCL overdensities. The overall pattern of the HIMF closely aligns with the ALFALFA HIMF. Additionally, I estimated upper limit overdensity values of 3.5 ± 1.6 and 1.8 ± 2.4 in the inner ZOA for W1 and W2, respectively. The accomplishments of the MIGHTEE-H I Early Science survey, Vela–SMGPS, and Vela–H I oer a promising glimpse into the immense capabilities that await H I science with the forthcoming SKA